2013
DOI: 10.3389/fpsyg.2013.00037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Role of Attention in the Context of Unconscious Thought Theory: Differential Impact of Attentional Scope and Load on Preference and Memory

Abstract: Attention is a key process used to conceptualize and define modes of thought, but we lack information about the role of specific attentional processes on preferential choice and memory in multi-attribute decision making. In this study, we examine the role of attention based on two dimensions, attentional scope and load on choice preference strength and memory using a paradigm that arguably elicits unconscious thought. Scope of attention was manipulated by using global or local processing during distraction (Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
4
11
0
Order By: Relevance
“…Sometimes not attending to part of the information or relying on small samples can prove useful (Gigerenzer & Gaissmaier 2011). The differences in selection (changes in scope of attention) could also affect utilization of the cues and would be consistent with results showing that changes in scope of attention can affect preference strengths and memory (Srinivasan et al 2013).…”
Section: Tim Rakowsupporting
confidence: 72%
See 3 more Smart Citations
“…Sometimes not attending to part of the information or relying on small samples can prove useful (Gigerenzer & Gaissmaier 2011). The differences in selection (changes in scope of attention) could also affect utilization of the cues and would be consistent with results showing that changes in scope of attention can affect preference strengths and memory (Srinivasan et al 2013).…”
Section: Tim Rakowsupporting
confidence: 72%
“…The changes in (perceptual or conceptual) scope of attention under different situations enable us to sample and process information differently leading to differences in processes involved in memory and decision making. Using the UTT paradigm, we manipulated the distraction task using global or local processing (associated with changes in scope) at low and high levels of cognitive or working memory load (Srinivasan et al 2013). We found that global processing during distraction resulted in stronger preference for the chosen item irrespective of cognitive load.…”
Section: Tim Rakowmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, we propose that the putative 'unconscious thought' is constrained by differences in the attentional processes employed during distraction Srinivasan et al, 2013) depending on the weights of the cues and past experience of their validity. Sometimes not attending to part of the information or relying on small samples can prove useful (Gigerenzer & Gaissmaier, 2011).…”
mentioning
confidence: 99%